Diffusion of the e-SUS Primary Care innovation in Family Health Teams - Talita Ingrid Magalhães Silva; Ricardo Bezerra Cavalcante; Regina Consolação dos Santos; Tarcísio Laerte Gontijo; Eliete Albano de Azevedo Guimarães; Valeria Conceição de Oliveira
ABSTRACT Objective: To analyze the diffusion of e-SUS Primary Care innovation in Family Health Teams. Method: A qualitative approach case study, based on Innovation Diffusion Theory and Technology Acceptance Model. We conducted 62 interviews and observation of professionals from Family Health Teams in six municipalities of Minas Gerais State, between March 2016 and January 2017. The data were treated through Categorical Thematic Content Analysis and, systematized, with Atlas.ti software . Results: It was verified that although the e-SUS Primary Care strategy is recognized as a technological innovation, situations predominate that weaken its acceptance as: incompatibilities with the work process; sudden deployment, poor training; work overload; resistance; and negative impacts on health care. Conclusion: The diffusion of the e-SUS Primary Care strategy as a technological innovation has presented potential situations of its rejection, conforming as challenges to be overcome.